Velocidade de absorção do glufosinate e seus efeitos em plantas daninhas e algodão - Silva, Ilca Puertas de Freitas e [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
O glufosinate é um herbicida derivado do fosfinotricina, uma toxina microbiana natural isolada a partir de duas espécies de fungos do gênero Streptomyces. O mecanismo de ação é a inibição direta da enzima glutamina sintetase, que resulta no aumento da concentração de amônio, sendo tóxico para as células. A pesquisa teve como objetivo avaliar a velocidade de absorção do glufosinate e seus efeitos em plantas daninhas e na cultura do algodão. O experimento foi conduzido em casa-de-vegetação com o cultivar de algodão FiberMax 910 e as plantas daninhas Brachiaria decumbens e Ipomoea grandifolia plantadas em vasos. O experimento foi instalado com duas formulações do herbicida, glufosinate de amônio (2,0 L p.c. ha-1) e glufosinate de potássio (2,0 L ha-1), cinco períodos sem a ocorrência de chuvas (1; 3; 6; 24 e 48 horas após aplicação) e uma testemunha sem aplicação com quatro repetições por tratamento. As plantas para as análises laboratoriais foram coletadas com dois dias após aplicação, quando começaram a aparecer os primeiros sintomas de intoxicação visual. As variáveis analisadas foram teor de amônia, glutamato, glutamina e glufosinate; sintomas de intoxicação visual e taxa de transporte de elétrons (ETR). Foi observado...

Glufosinate is derived of phosphinothricin, a natural microbial toxin isolated from two species of the Streptomyces fungus. The mechanism of action is through direct inhibition of the glutamine synthetase enzyme, which results in the increase of ammonium concentration, becoming toxic to the cells. The objective of this study was to evaluate the rate of absorption of glufosinate and its effects on weeds and cotton culture. The experiment was conducted in a green house, the cultivar of cotton FiberMax 910, Brachiaria decumbens and Ipomoea grandifolia planted in 5 liter pots. The experiment was conducted with two formulations of the herbicide, glufosinate ammonium (2.0 pc L ha-1) and glufosinate potassium (2.0 L ha-1), five periods without rainfall (1, 3, 6, 24 and 48 hours after application) and an untreated control with all treatments were replicated four times. The plants for laboratory analysis were collected within 2 days after application, when the first visual symptoms of intoxication began to appear. The analyzed variables were the ammonia content, the content of compounds that belongs to the glufosinate metabolic route (glutamate and glutamine), glufosinate content, visual symptoms of intoxication and electron transport rate (ETR). It was observed that the absorption of glufosinate occurs within 48 hours of application for both formulations and evaluated species. The amount of ammonia in the commercial formulation did not interfere with ammonia levels observed in intoxicated plants. The highest levels of ammonia for cotton occurred at 5 hours without rain, and for B. decumbens and I. grandifolia with 6 hours without rain. We have observed a significant reduction of glutamate and glutamine in plants treated with the two formulations of glufosinate, with the lowest levels found in cotton and B. decumbens carried out in... (Complete abstract click electronic access below)
Keywords: Algodão; Plantas - Efeito dos herbicidas; Algodão - Fisiologia; Erva daninha - Controle; Toxinas microbianas; Absorção (Fisiologia); Microbial toxins; Plants, Effect of herbicides; Absorption (Physiology)